Regulation of Brain Proteolytic Activity Is Necessary for the In Vivo Function of NMDA Receptors - Kvajo, Mirna (J Neurosci, 2004)
Serine proteases are considered to be involved in plasticity-related events in the nervous system, but their in vivo targets and the importance of their control by endogenous inhibitors are still not clarified. Here, we demonstrate the crucial role of a potent serine protease inhibitor, protease nexin-1 (PN-1), in the regulation of activity-dependent brain proteolytic activity and the functioning of sensory pathways. Neuronal activity regulates the expression of PN-1, which in turn controls brain proteolytic activity. In PN-1(-/-) mice, absence of PN-1 leads to increased brain proteolytic activity, which is correlated with an activity-dependent decrease in the NR1 subunit of the NMDA receptor. Correspondingly, reduced NMDA receptor signaling is detected in their barrel cortex. This is coupled to decreased sensory evoked potentials in the barrel cortex and impaired whisker-dependent sensory motor function. Thus, a tight control of serine protease activity is critical for the in vivo function of the NMDA receptors and the proper function of sensory pathways.